2019
DOI: 10.21608/ejbo.2019.8026.1289
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Impact of Seed Priming with CaCl2 or Carrot Root Extract on Lupinus termis Plants Fully Grown under Salinity Stress

Abstract: S EEDS of Lupinus termis (cv. Gemmeza R 2) were primed by presoaking for six hr in 100% aqueous extract of carrot roots or 10mM CaCl 2 solution, sown and left to grow for 30 days on clay-sandy soil (2:1 w/w). Seven-day-old seedlings grown from primed and unprimed seeds were exposed to salinity stress at 150mM NaCl. Salinity stress caused decreases in lengths, fresh and dry weights of roots and shoots, leaf water content and photosynthetic pigments. Total soluble sugars, proteins, alkaloids, malondialdehyde (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Among others, they attributed the improved K + /Na + ratio and membrane integrity to antioxidants and polyphenols rich seed extracts. Analogous results have been reported in case of Phaseolus vulgaris, Vicia faba, Triticum aestivum, Lupinus termis , and Zea mays plants subjected to varying degree of salt concentrations ( Rady and Mohamed, 2015 ; Latif and Mohamed, 2016 ; Latef et al, 2019 ; Nessim and Kasim, 2019 ; Aboualhamed and Loutfy, 2020 ; ur Rehman et al, 2021 ). In another study, presence of phenols, flavonoids, and AsA in Rosmarinus officinalis L. extracts was associated to salinity alleviation in apple seedlings ( Mahmoudand and Dahab, 2018 ).…”
Section: Use Of Plant Extracts Against Salinitysupporting
confidence: 81%
See 2 more Smart Citations
“…Among others, they attributed the improved K + /Na + ratio and membrane integrity to antioxidants and polyphenols rich seed extracts. Analogous results have been reported in case of Phaseolus vulgaris, Vicia faba, Triticum aestivum, Lupinus termis , and Zea mays plants subjected to varying degree of salt concentrations ( Rady and Mohamed, 2015 ; Latif and Mohamed, 2016 ; Latef et al, 2019 ; Nessim and Kasim, 2019 ; Aboualhamed and Loutfy, 2020 ; ur Rehman et al, 2021 ). In another study, presence of phenols, flavonoids, and AsA in Rosmarinus officinalis L. extracts was associated to salinity alleviation in apple seedlings ( Mahmoudand and Dahab, 2018 ).…”
Section: Use Of Plant Extracts Against Salinitysupporting
confidence: 81%
“…They can be prepared either from a whole plant or from any specific part of the plant, i.e., fruits, flowers, bark, roots, leaves, stems, seeds, pollens, grains, etc. ( Semida and Rady, 2014 ; Lorenzo et al, 2019 ; Nessim and Kasim, 2019 ; Rady et al, 2019a ; Zulfiqar et al, 2020b ; Suryaman et al, 2021 ). Whereas plant derived products like protein hydrolyzates, polyamines, polyols, amides, etc.…”
Section: Use Of Plant Extracts Against Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The generated reactive oxygen species caused severe damage to plant cells through the destruction of cell membranes, which results in an increase of malondialdehyde content. In our study, the reported increase in MDA and H 2 O 2 contents in barley leaves is due to the fact that many components, including protein and lipids, join the formation of the plant cell membranes, and salt stress breaks these components down within the cell membranes as a result of the increased development of ROS, which also affects other cellular components, such as carbohydrates and protein [ 6 , 94 , 95 , 96 ]. Endophytic fungi play a major role in combating abiotic stresses, specifically salinity stress [ 53 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…61, No. 1 (2021) RASHA KAMAL HELMEY Nessem & Kasim (2019) mentioned that among the more deleterious effects of salinity stress on plants are the significant reductions in various growth parameters (Rahneshan et al, 2018).…”
Section: Leaf Areamentioning
confidence: 99%